Designing and implementing methodology for double-blind, placebo-controlled clinical trials using blood products within the Department of Veterans Affairs. (April 2022) - Miller, Elliott K; Goldberg, Alexa M; Janoff, Edward N; Brown, Sheldon T; Curtis, Jeffrey L; Bonomo, Robert A; Shih, Mei-Chiung; Gleason, Theresa C
Background: Success in conducting clinical trials during the coronavirus disease of 2019 pandemic requires the ability to innovate and adapt. There are well-established procedures for the blinding of investigational agents, especially medications, in placebo-controlled randomized clinical trials within the Veterans Health Administration. However, these procedures, managed by research pharmacists, may not apply to investigational agents that are not exclusively managed by pharmacy, such as blood products, including coronavirus disease of 2019 convalescent plasma (plasma). In the absence of established blinding procedures, such studies require special design considerations to minimize uncertainty or bias. Methods: We describe the processes and procedures developed for blinding of plasma in "Veterans Affairs CoronavirUs Research and Efficacy Studies-1" as a prototypical study using this class of investigational therapeutic agents. Veterans Affairs CoronavirUs Research and Efficacy Studies-1 is an ongoing multicenter randomized clinical trial testing the efficacy of plasma added to conventional therapy for severe acute respiratory syndrome coronavirus-2 infection. Results: We report the design of procedures to supply investigational blood products or 0.9% normal saline (saline) control while ensuring the integrity of the blind. Key aspects include workflow considerations, physical blinding strategies, and methods for engaging stakeholders. These procedures leverage the well-established Veterans Affairs research pharmacist's research infrastructure, and Blood Bank Services, which is responsible for blood-based investigational products. Conclusion: By describing the methods used to deliver blood products in a blinded manner in Veterans Affairs CoronavirUs Research and Efficacy Studies-1, we strive both to educate and to increase awareness to improve the implementation of these biological therapeutics for future, high-quality research studies.